Immersive virtual reality as a tool to learn problem-solving skills. (April 2021) - Araiza-Alba, Paola; Keane, Therese; Chen, Won Sun; Kaufman, Jordy
Abstract: Immersive virtual reality (IVR) technology has demonstrated positive educational outcomes related to its use and is gaining traction in educational and training settings; IVR is expected to have widespread adoption within the classroom in the upcoming years. However, the educational potential of IVR with children has not been thoroughly investigated, especially as a tool for problem-solving skills. Therefore, this study was designed to answer the following questions: (1) Is IVR a useful tool to learn and practice problem-solving skills? More specifically, do children using IVR solve a game better than those using a tablet application or a board game? (2) Does IVR provide a more engaging experience for children to practice problem-solving skills than on a tablet or a board game? (3) Do problem-solving skills learned with IVR technology transfer to real-life (physical game)? Children ( n  = 120) aged 7–9.9 years were randomly assigned to a problem-solving game in one of three conditions: board game, tablet, or IVR. The results showed that, overall, the percentage of children who completed the problem-solving game was higher in the IVR condition (77.5%), compared with those in the tablet (32.5%) or board game (30%) conditions. We also found that the interest and enjoyment scores of participants using IVR were significantly higher than participants in the other two conditions, and that the children in the IVR condition were able to learn how to solve the problem and transfer their learning to the physical game. IVR is a technology capable of engaging interest and motivating the user, as well as having the potential to assist in cognitive processing and knowledge transfer. Highlights: IVR technology is a useful tool to learn and practice problem-solving skills. Children were more engaged by the IVR technology than traditional teaching methods. IVR has the potential to assist with cognitive processing and knowledge transfer. The natural feeling that IVR offers to the user could reduce their cognitive load.